Magnetic Characteristics of Some Yamato Meteorites─Magnetic Classification of Stone Meteorites─ - Nagata, Takesi; Sugiura, Naoji (1976)
P(論文) 13 Yamato stone meteorites have been magnetically examined. They are one enstatite chondrite (E), 6 olivine-bronzite chondrites (H), 2 olivine-hypersthene chondrites (L), one carbonaceous chondrite (C) and 3 achondrites (aC). The intrinsic magnetic parameters of these stone meteorites obtained from their magnetic hysteresis curves and thermomagnetic curves, together with those of other 7 known chondritic meteorites, are specifically examined in terms of the compositional and petrographical classification of stone meteorites. The saturation magnetization (I_s) and major magnetic transition temperature (Θ_c) in the cooling process can be taken as the representative magnetic parameters in the proposed magnetic classification of stone meteorites. In the I_s versus Θ_c diagram, those examined stone meteorites, 25 in total, are separated into groups namely, I_s (E) > I_s (H) > I_s (L) > I_s (aC), Θ_c (H and L) < Θ_c (E and aC) ≃ 770℃, I_s (C) ≃ I_s (L) but Θ_c (C) < 600℃ < Θ_c (L). Although the boundary between the L-group and the H-group is not sharp enough in the I_s-Θ_c diagram, the L-group chondrites contain a distinctly larger amount of plessite phase which can be magnetically identified. departmental bulletin paper